Thermal and hydraulic characteristics of microchannel heat sinks with cavities and fins based on field synergy and thermodynamic analysis. (5th July 2020) - Li, Yifan; Wang, Zhipeng; Yang, Junlan; Liu, Hanqiao
Highlights: Novel MCHSs with isosceles triangular cavities and different fins are proposed. The effect of the fin shape is optimized for overall performance improvement. The heat transfer enhancement is explored from the field synergy principle. The thermodynamic performance is analyzed by the entropy generation. The MCHS ITC-FDF presents the superior comprehensive performance. Abstract: Novel microchannel heat sinks (MCHSs) with cavities and fins are put forward for the cooling demand of microelectronic devices with high heat production. The flow and convective heat transfer of the microchannels with isosceles triangular cavities and four different fins, including rectangular fins, streamlined fins, backward drop-shaped fins and forward drop-shaped fins, are studied numerically for Reynolds number ( Re ) ranging of 173–635, i.e. flow rate ( Q v ) ranging of 12–54 ml/min. Firstly, the combined effect of the cavities and fins on the thermal and hydraulic characteristics is analyzed. Secondly, the field synergy principle is adopted to explore the synergy between the fluid temperature and velocity fields; the entropy generation is used to investigate the thermodynamic performance and the irreversibility for different MCHSs in terms of second law of thermodynamics. Lastly, the effect of fin shape on the comprehensive performance of the complex MCHSs is evaluated based on thermal resistance and performance evaluation criterion ( PEC ). Results indicate that the novel designs present conspicuous heat transfer improvement owing to the redevelopment of boundary layer, intensive secondary flow and effective chaotic mixing compared to conventional rectangular microchannel (R). According to the field synergy principle and thermodynamic analysis, the superior thermal performance of the novel MCHSs can be attributed to the improved synergy between the temperature and flow fields, and the reduction of total irreversible loss. But the micro structures lead to the mainstream separation, acceleration and disturbance, which increase the pressure drop and friction loss. Nevertheless, the comprehensive performance of the complex MCHSs has been improved obviously compared to the conventional one. Among the novel heat sinks, the microchannel with isosceles triangular cavities and forward drop-shaped fins acquires the greatest overall performance with PEC  = 1.617 at Q v  = 36 ml/min, with the advantage of the notably enhanced thermal performance accompanied by the acceptable pressure drop.